TURNING TRASH INTO TREASURE: WASTE BANKS DRIVING CIRCULAR ECONOMY THROUGH COFFEE, PLASTIC, AND OIL WASTE MANAGEMENT - Gautama Sastra Waskita (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Waste management is a critical challenge in Indonesia, where plastic waste, coffee waste, and used cooking oil contribute significantly to environmental pollution. This study explores the potential of waste banks to integrate these diverse waste streams into a cohesive circular economy framework. The research aims to assess the operational, environmental, and socio-economic benefits of waste banks that manage coffee waste, plastic waste, and used cooking oil in Indonesia. A qualitative research design, including case studies, interviews, and focus group discussions, was employed to gather insights from waste bank operators, community members, and experts. The findings reveal that waste banks can successfully diversify their operations by recycling plastics, composting coffee waste, and converting used cooking oil into biodiesel. This integrated approach contributes to waste reduction, environmental sustainability, and community empowerment through green job creation. However, challenges such as limited infrastructure, policy support, and community awareness remain barriers to full implementation. The study recommends policy development, investment in technology, and enhanced community engagement to optimize waste bank operations and promote circular economy practices.